(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article analyzes modern trade formats (hypermarket, supermarket,boutique, convenience store, deli, department store, warehouse store, secondhand, cash&carry), notes the influence on the change of trade formats in Ukraine under the influence of it, investigates the development of shops of the «Vape Shop» type, based on the analysis of foreign literature sources, describes examples of the successful application of modern marketing approaches to the creation of new trade formats: facial recognition , virtual reality, experimental stores, the role of franchising in the creation of new formats of trade is substantiated and it is emphasized that the use of social networks is a powerful marketing tool for franchise business, significant attention is paid to the issue of green trade and its impact on consumers, the impact of investments in private entrepreneurship and trade in particular is shown, it was emphasized that one of the key areas where entrepreneurs use artificial intelligence is personalization. AI enables the analysis of large volumes of consumer data and the creation of personalized recommendations that help increase sales and improve the customer experience.a conclusion is drawn about the expediency of applying new marketing approaches in the practice of domestic trade.